Agencia para el acompañamiento en los hogares de infantes en la ciudad de Santiago de Cali “DULCE COMPAÑÍA” (2011)
According to the needs and demands of society, in which most parents have little involvement in the lives of their children by multiple factors such as work, social life, study, the absence of responsibility, group problems, among others, thus generating most of the problems of the youth population in schools of Cali such as alienation, emotional and psychological problems, bladder control, aggression, anxiety, noncompliance, and increased rates of obesity, among others. We have developed this project a proposal that aims to address the problem of “care and attention” required by children due to the temporary absence of their parents by creating a professional nanny agency which applies Conceptual Pedagogy, that aims to provide a supporting solution based on love and affection which creates trust in parents, providing care in both physical and emotional development, intellectual, artistic and other skills of their children, through a portfolio of services to suit the needs of households. This proposal will target children between 0 and 7 years of strata 5 and 6 of the city Santiago de Cali.